2013
DOI: 10.1021/la403454p
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin-Bearing Gold Glyconanoparticles for the Development of Site Specific Drug Delivery Systems

Abstract: Three novel gold nanoparticles containing multiple long, flexible linkers decorated with lactose, β-cyclodextrin, and both simultaneously have been prepared. The interaction of such nanoparticles with β-d-galactose-recognizing lectins peanut agglutinin (PNA) and human galectin-3 (Gal-3) was demonstrated by UV-vis studies. Gal-3 is well-known to be overexpressed in several human tumors and can act as a biorecognizable target. This technique also allowed us to estimate their loading capability toward the antican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 60 publications
0
52
2
Order By: Relevance
“…For instance, cyclodextrin-modified gold nanoparticles have been applied to construct versatile platform via host−guest interaction for targeted drug delivery conveniently. 31,32 Herein, a multifunctional nanocomposite based on β-cyclodextrin-modified gold nanoparticle (AuNP@CD) was delicately designed and fabricated for cancer-targeted therapy with intracellular pH-triggered drug delivery. As shown in Scheme 1, the peptidic derivative adamantane−PEG 8 −glycine− arginine−glycine−aspartic−serine (AD-PEG 8 -GRGDS) and the adamantane conjugated anticancer drug doxorubicin with hydrazone bond linkage (AD-Hyd-DOX) were decorated on the surface of AuNP@CD via host−guest interaction simultaneously, forming multifunctional nanocomposite AuNP@CD-AD-DOX/RGD.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, cyclodextrin-modified gold nanoparticles have been applied to construct versatile platform via host−guest interaction for targeted drug delivery conveniently. 31,32 Herein, a multifunctional nanocomposite based on β-cyclodextrin-modified gold nanoparticle (AuNP@CD) was delicately designed and fabricated for cancer-targeted therapy with intracellular pH-triggered drug delivery. As shown in Scheme 1, the peptidic derivative adamantane−PEG 8 −glycine− arginine−glycine−aspartic−serine (AD-PEG 8 -GRGDS) and the adamantane conjugated anticancer drug doxorubicin with hydrazone bond linkage (AD-Hyd-DOX) were decorated on the surface of AuNP@CD via host−guest interaction simultaneously, forming multifunctional nanocomposite AuNP@CD-AD-DOX/RGD.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 2 [36], 3[31,32], 15 [36] and 16 [36] were synthesized as previously reported. Human galectin-3 was expressed and purified as previously reported [45].…”
Section: General Methodsmentioning
confidence: 99%
“…Despite the most common carriers are based on nano- and microparticles (i.e., albumin, poly(lactic- co -glycolic acid)-PLGA NPs, liposomes), many examples in literature report on the development of gold-based glyco nanoparticles as efficient system to delivery payloads. In this contest, AuNPs modified with lactose moieties and β-cyclodextrins have been reported by Vargas-Berenguel et al [87]. The authors showed that GAuNPs were still able to recognize specific lectin (peanut agglutinin, PNA) and human galectin-3 (Gal-3), exploiting multiple lactose residues displayed on gold surface.…”
Section: Reviewmentioning
confidence: 96%